Pengaruh Kepempinan dan Budaya Organisasi Terhadap Pengembangan Usaha Berbasis Syariah di Kalangan Washliyin Propinsi Sumatera Utara - . Burhanuddin (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2021)
Al Jam'iyatul Washliyah organization abbreviated Al-Washliyah (AW) was established in Medan on November 30, 1930 to coincide with the 9th of Rajab 1349 H. A name of the largest Islamic community organization in North Sumatera Province, and the third largest in Indonesia after NU and Muhammadiyah. Although Al-Washliyah has businesses, it cannot yet be economically independent. This study tries to explain by looking for information on how the influence of leadership and organizational culture on the development of sharia-based enterprises in Washliyin North Sumatera Province. The research method used is qualitative research methods, while the data collection techniques used are field research which includes observation and interviews, as well as literature. The results of this study indicate that on the one hand leadership has a positive effect on the development of sharia-based businesses in Washliyin North Sumatra Province, for example, has been able to make new innovations by establishing Islamic banks PT. BPR Syariah Al-Washliyah that has never existed before. On the other hand there are still weaknesses in leadership, have not been able to enforce regulations according to demands, as a result the efforts have not been fully ordered by the organization and orderly administration. For example, there are businesses that don't work and eventually close, namely the Al-Washliyah hospital / clinic in 2004. Then there has been a shift in the value of organizational culture, the decline of the ulama tradition in Washliyin circles, and the entry of the Al-Washliyah leadership elite from politicians. This also affected the development of sharia-based businesses in Washliyin, North Sumatra Province